Motor current signature analysis-based non-invasive recognition of mixed eccentricity fault in line start permanent magnet synchronous motor - Karami, Mahdi; Mariun, Norman; Ab Kadir, Mohd Zainal Abidin; Misron, Norhisam; Mohd Radzi, Mohd Amran (Taylor and Francis Group, 2021)
In this study, a cost-effective and non-invasive detection strategy is proposed for three-phase line start permanent magnet synchronous motor (LSPMSM) under mixed eccentricity fault using motor current signature analysis. In this respect, theory of air gap magnetic field in eccentric LSPMSM is presented. The detection strategy is examined through modeling and experimental studies. Two-dimensional time stepping finite element method is employed to calculate the motor parameters. Effects of mechanical load and fault severity on eccentric LSPMSM are also investigated. Different fault-related components are scrutinized and the most effective features are identified for this new type of electrical motor. The results indicate that amplitudes of fault-related components at rotor frequency are precise for early detection of mixed eccentricity in LSPMSM. Finally, an efficient frequency pattern as well as detection criterion is specified.